Differences in Competitiveness of the Construction Enterprises in Czech Republic and Austria (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The paper is aimed at analysis in the areas of strategic management, competitive position and decision-making in small and medium-sized construction enterprises according to their managers. It presents the results of the survey conducted in Czech Republic and Austria. The results are mutually compared and the differences between the enterprises and their managers are identified. For the questionnaire survey two approaches were used, namely resource-based view and the market-based view, for the identification of the competitive position of the enterprises. There are also questions focused on propositions for manager’s decision-making. All the acquired results are statistically evaluated with appropriate commentaries. Relationships between those areas in each enterprise provides better understanding of mutual dependence of strategic management, decision-making and competitive analysis. It also provides evidence of different approach of the Czech and Austrian enterprises in analysed areas. Results can be used by managers to understand links and different approaches to those areas in Czech and Austrian small and medium-sized construction enterprises.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.